Modelling and validation of TBR Hydrodynamics: Local comparison between CFD and experiments. (1st October 2020) - Uribe, Sebastián; Al-Ani, Mohammed; Cordero, Mario E.; Al-Dahhan, Muthanna
Highlights: A multiphase CFD model of a TBR was implemented with a resolved-particle approach. The model incorporates a resolved-particle approach for the solid phase description with 2695 solid particles. An experimental validation study was performed using in-house developed advanced measurement techniques. Local velocity and saturation diameter profiles were experimentally measured at different conditions. The model predicts the experimentally measured local profiles with a precision up to 93% Abstract: A Computational Fluid Dynamics (CFD) and validation experimental study was conducted for a packed column where two fluid phases flow downward in a trickle regime. In the model, the explicit description of the solid packing was incorporated in order to account for the textural characteristics of the bed through a resolved-particle approach, and the momentum balances for the two fluid phases were solved in the void space between the packing. The models were implemented in the commercial software COMSOL Multiphysics 5.3a. In the experimental setup, the local liquid velocity and liquid saturation diameter profiles at three different location in the column height were determined using optical fiber probes. These experimentally determined profiles were used to validate the local predictions of the CFD model, which considered the two-phase hydrodynamics and the three-phase interaction forces through interfacial momentum exchange closures. The results show that the CFD model can properly predict the local variation of the liquid velocity at different flow rate conditions, with an average absolute error below 18.6%. The CFD model properly predicted the liquid maldistribution observed in the experimental measurements. Furthermore, the CFD model results allowed to study other local phenomena, such as bypass channeling and backmixing; and also allowed to determine the variations in the interaction forces between the phases.